Evaluation Of Some Locally Available Inks In Nepal For Staining Arbuscular Mycorrhiza - Chhetri, BK; Maharjan, S (Kathmandu University Journal of Science, Engineering and Technology, 2012)
Two inks locally available in Nepal (Chelpark permanent black and Chelpark washable royal blue) were tested for staining arbuscular mycorrhiza. Both the inks stained all structures (arbuscules, vesicles and internal hyphae) successfully. The tested inks are economically feasible and thus may encourage research activities related to arbuscular mycorrhiza in Nepal. DOI: http://dx.doi.org/10.3126/kuset.v8i1.6040 KUSET 2012; 8(1): 33-35